EMOTIONAL INTELLIGENCE AND OCCUPATIONAL HEALTH IMPACT ON EMPLOYEE PERFORMANCE - Chamdan Purnama (Universitas Mercu Buana, 2017)
Abstract. This study aimed to analyze the influence of emotional intelligence andoccupational health either partially or simultaneously on the employee's performance.This type of research is correlational. The population of this study are employees CV.Fajar Offset Mojokerto, with a population of about 80 employees. Data was collectedby using a questionnaire that had been tested for validity and reliability. The dataanalysis used regression analysis with SPSS version 23. Based on the results of theregression analysis, it was found that emotional intelligence and occupational healthsimultaneously affect the performance of employees and also it was found thatoccupational health and emotional intelligence partial effect on employee performance.In this regard then, the company needs to provide additional training, especially for theself-development of emotional intelligence and maintain employees' health in order toimprove employee performance and build productivityKeywords: Emotional Intelligence, Occupational Health, Employee performance.